A Survey On Students Atitude Toward Recreational Reading Materials - Ivy, Michael Toda Sanub (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study sought to look into Students' Attitudes towards Recreational Reading Materials. The study is important as it can give related parties insights into to related parties or students interest towards recreational reading materials. It is with much hope that the findings can give teachers and educators to be able to help students to motivate students to enhance their reading interest to become intended readers. Since the study a attempts to provide some insights into the motivation or factors of the students recreational reading materials within their outside classroom. It will provide teachers with clearer understanding on how students are being motivated and interested in becoming independent readers There were 289 questionnaires that were given and been administered to the students concern where it looked into the students' attitudes toward recreational reading materials, kinds of recreational reading materials that they are interested and factors that affected their attitudes recreational reading materials. The result showed that there were positive feedback from the respondents on their attitudes toward recreational reading materials.